Nitrogen uptake, grain yield, and oil concentration of dwarf castor beans under nitrogen rates and inoculation of rhizobacteria in grasses–legumes rotation - Gato, Isabela Martins Bueno; Oliveira, Carlos Eduardo da Silva; Jalal, Arshad; Moreira, Vitória de Almeida; Hashem, Amr H.; de Lima, Bruno Horschut; Leite, Gabriel da Silva; Al-Askar, Abdulaziz A.; Freitas, Leandro Alves; AbdElgawad, Hamada; Ferreira, Selton Vinicius Domingos; Santana, Leticia de Jesus; et al. (Frontiers in Microbiology, 2024)
Plant growth-promoting bacteria (PGPBs) has primarily studied for atmospheric nitrogen (N) fixation but it also has the capacity to improve nutrition and yield of crop plants.Therefore, the objective of this research was to investigate the effects of inoculation with PGPBs in association with different N rates on N uptake, grain yield and oil concentration of dwarf castor beans in succession to legumes and grasses in Ilha Solteira, Brazil. The treatments consisted of N rates (0 to 180 kg ha -1 of N) and inoculation with three plant growth-promoting bacteria (Azospirillum brasiliense, Bacillus subtilis and Pseudomonas fluorescens, applied by leaf) and a control with no-inoculation. The grain and oil yields of castor beans were increased by 20 and 40% at the rate of 103 kg ha -1 of N in succession to grasses as compared to without N application. In addition, grain yield of castor bean after legumes was increased by 28, 64 and 40% with estimated rates of 97, 113 and 92 kg ha -1 of N in combination with inoculations of A. brasilense, B. subtilis and P. fluorescens Field Code Changed as compared to without N application, respectively. Shoot, grain, and total N uptake were improved with foliar inoculation of A. brasilense, B. subtilis and P. fluorescens at the N rates of 45, 90 and 135 kg ha -1 respectively. Topdressing of N at the rate of is 103 kg ha - 1 and foliar inoculation in succession to grasses and 180 kg ha -1 of N without the effect of foliar inoculation in succession to legumes are recommended for higher grain and oil yield of castor beans. Foliar inoculations with A. brasilense, B. subtilis and P. fluorescens increased grain yield under reduced use of N fertilizer by 44, 37 and 49% in dwarf castor cultivation in succession to legumes, potentially contribute to sustainable agriculture.